Living in the waterfalls: A new species of Trichomycterus (Siluriformes: Trichomycteridae) from Tabay stream, Misiones, Argentina - Teran, Guillermo Enrique (2017)
A new species assigned to the genus Trichomycterus from the area of the waterfalls of Tabay stream, Paraná River basin, Misiones, Argentina, is described. Trichomycterus ytororo sp. nov. is distinguished from all other species in the genus by the presence of 31?35 dorsal procurrent caudal-fin rays and the combination of some external characters such as: coloration, number of pectoral?fin rays and pores of the laterosensory canals. The new taxon belongs to a presumably monophyletic group of species composed of T. crassicaudatus, T. igobi, and T. stawiarski based on the presence of 24 or more thickly ossified and rigid procurrent caudal-fin rays with a slender distal tip extending along the tips of at least ten neural spines.